Assessment of sorghum genetic resources of Ethiopia for anthracnose (Colletotrichum sublineolum Henn.) resistance and agronomic traits. Issue 11 (24th September 2019) - Mengistu, Girma; Shimelis, Hussein; Laing, Mark; Lule, Dagnachew
Abstract: Sorghum anthracnose caused by Colletotrichum sublineolum Henn. is one of the key diseases limiting sorghum production and productivity. Development of anthracnose‐resistant sorghum genotypes possessing yield‐promoting agronomic traits is an important breeding goal in sorghum improvement programs. The objective of this study was to determine the responses of diverse sorghum genetic resources for anthracnose resistance and agronomic traits to identify desirable lines for breeding. A total of 366 sorghum collections and three standard checks were field evaluated during the 2016 and 2017 cropping seasons. Lines were artificially inoculated with a virulent pure isolate of the pathogen. Anthracnose disease severity was assessed to calculate the area under disease progress curve (AUDPC). Agronomic traits such as panicle length (PL), panicle width (PW), head weight (HW) and thousand grain weight (TGW) were measured. Lines showed highly significant differences ( p < .001) for anthracnose severity, AUDPC and agronomic traits. Among the collections 32 lines developed levels of disease severity between 15% and 30% in both seasons. The following sorghum landraces were selected: 71708, 210903, 74222, 73955, 74685, 74670, 74656, 74183, 234112, 69412, 226057, 214852, 71420, 71484, 200126, 71557, 75120, 71547, 220014, 228179, 16212, 16173, 16133, 69088, 238388, 16168 and 71570. These landraces had a relatively low anthracnose severity possessing farmer‐preferred agronomic traits. The selected genotypes are useful genetic resources to develop anthracnose‐resistant sorghum cultivars.